ChemInform Abstract: Unified Approach to the Spiro(pyrrolidinyl‐oxindole) and Hexahydropyrrolo[2, 3‐b]indole Alkaloids: Total Syntheses of Pseudophrynamines 270 and 272A. Issue 17 (April 2016) - De, Subhadip; Das, Mrinal Kanti; Bhunia, Subhajit; Bisai, Alakesh
Abstract: An enantioselective 3‐hydroxymethylation of 3‐substituted oxindoles is described.